2021
DOI: 10.1021/acsearthspacechem.1c00320
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Relationship between Lake Urmia Saline Lakebed Emissions and Wet Deposition Composition in the Caucasus Region?

Abstract: One of the most significant environmental catastrophes throughout the Middle East and Caucasus region has been the desiccation of Lake Urmia, the world second-largest hypersaline lake. This lake has lost approximately two-thirds of its water volume since 1999, resulting in increased exposure of lacustrine deposits that are considered as a new aerosol source. This in situ study investigates for the first time the spatial distribution of water-soluble ion concentrations (Cl–, Br–, NO2 –, NO3 –, SO4 2–, methanesu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 109 publications
0
9
0
Order By: Relevance
“…Earlier works by Ahmady‐Birgani et al. (2020, 2021) and Ravan et al. (2019) reported elevated values of these elements and species in nearby locations to Lake Urmia (i.e., Golmankhaneh, Salmas, and Ashk Island).…”
Section: Resultsmentioning
confidence: 90%
See 4 more Smart Citations
“…Earlier works by Ahmady‐Birgani et al. (2020, 2021) and Ravan et al. (2019) reported elevated values of these elements and species in nearby locations to Lake Urmia (i.e., Golmankhaneh, Salmas, and Ashk Island).…”
Section: Resultsmentioning
confidence: 90%
“…In sum, unlike the winter season that contains the lowest values of marine components, the highest concentration of these ions appears in March, April, May, and June (i.e., in the late winter to spring months). Earlier works by Ahmady-Birgani et al (2020, 2021 and Ravan et al (2019) reported elevated values of these elements and species in nearby locations to Lake Urmia (i.e., Golmankhaneh, Salmas, and Ashk Island). Meaning, rainwater samples have been affecting by marine elements and ions near 40km farthest from the Lake's shoreline.…”
Section: Monthly and Seasonal Variability In Different Directionsmentioning
confidence: 88%
See 3 more Smart Citations